Improving the quality condition of the structure of welded joints made of rotor steel - Dmytryk, V.V.; Skulsky, V.Yu.; Kasyanenko, I.V.; Vavilov, O.V.; Kantor, O.G. (Вопросы атомной науки и техники, 2022)
The solution to the problem of increasing the reliability and service life of the welded joint of the rotor involved obtaining its original structure with improved quality characteristics. Obtaining was achieved by improving the technology of automatic welding. This improvement was based on the performing the welding process on the optimized parameters of the mode, which provided the appropriate temperature regime of the one-piece connection that is made. Thus, the welding heat provided the formation of the original structure with higher quality characteristics in comparison with a similar structure obtained by the normal mode of welding. It was found that austenitic grains in the structure of the heat affected zone of the welded joint, which is heated above Аc₃, are smaller in size compared to similar grains in the structure of the standard technology. Accordingly, the new decay products of austenite in the area of heat affected zone, which is heated to the temperature range Ac₁ – Ac₃, were sorbitol and troostite. Thus, the proposed mode of automatic welding has increased reliability and increased by 10…15% of the life of the rotor.